Investigation of the adsorption of ions chromium by mean biochar from coniferous trees. - Frolova, L.; Фролова, Л.; Kharytonov, Mykola; Харитонов, Микола Миколайович; Klimkina, I.; Клімкіна, І.; Kovrov, O.; Ковров, О.; Koveria, A.; Коверія, А. ((KACST) in Riyadh, Saudi Arabia, 2021)
Biochar, obtained by pyrolysis of coniferous wood, as an adsorbent for removing chromium ions from aqueous solutions was used. Biochar samples were examined using X-ray, X-ray fluorescence analysis, DTA, TG, FT-IR, SEM microscopy. The ash composition was not significantly dependent on temperature and included Mg, Ca, Ti, P, C, O. X-ray phase analysis showed the presence of silicates, calcium and magnesium carbonates. IR spectroscopy confirmed the presence of organic groups. The adsorption experiments were carried out by varying the dosage of the adsorbent, the initial concentrations of chromium ions, and the contact time. The structure used biochar has no distinct pores apparently due to filling by nanoparticles chromium compound. To clarify the kinetic parameters and the mechanism of the adsorption process, kinetic models of first, second order and intra-particle diffusion were used. The kinetic model of the first order describes the kinetic curves in the best way. В якості адсорбенту для видалення іонів хрому з водних розчинів використано біовугілля, отримане піролізом деревини хвойних порід. Зразки біовугілля досліджували за допомогою рентгенівського, рентгенофлуоресцентного аналізу, DTA, TG, FT-IR, SEM мікроскопії. Склад золи істотно не залежав від температури і включав Mg, Ca, Ti, P, C, O. Рентгено-фазовий аналіз показав наявність силікатів, карбонатів кальцію та магнію. ІЧ-спектроскопія підтвердила наявність органічних груп. Адсорбційні експерименти проводили шляхом зміни дозування адсорбенту, початкової концентрації іонів хрому та часу контакту. Використана структура біовугілля не має чітко виражених пір, очевидно, через заповнення наночастинками сполуки хрому. Для уточнення кінетичних параметрів та механізму процесу адсорбції використано кінетичні моделі першого, другого порядку та внутрішньочасткової дифузії. Кінетична модель першого порядку найкраще описує кінетичні криві.
Дослідження адсорбції іонів хрому з використанням біовугілля хвойних дерев
Keywords: Biocha; біовугілля; Adsorption; адсорбція; Chromium ions; іони хрому; X-Ray fluorescence analysis; рентгено-флуоресцентний аналіз